The co-occurrence of potentially traumatic events (PTEs) and their associations with posttraumatic stress disorder (PTSD) in Indian and Malaysian adolescents - Enya, Redican; Maria Louison, Vang; Mark, Shevlin; Siti Raudzah, Ghazali; Ask, Elklit (Elsevier B.V., 2023)
Background: Although it is well-established that people can experience multiple traumatic events, there are few studies examining the co-occurrence of such experiences in non-Western nations. The current study sought to examine the occurrence of multiple potentially traumatic experiences (PTEs) and their associations with posttraumatic stress disorder (PTSD) among adolescents from two Asian nations. Methods: Latent class analysis (LCA) was employed to model the co-occurrence of PTEs in two school samples of adolescents from India (n =411) and Malaysia (n =469). Demographic correlates (i.e., sex, age, household composition, parent education) of the latent classes and the association between latent class membership and probable diagnosis of posttraumatic stress disorder (PTSD) were examined. Results: The LCA identified three latent classes for the Indian sample: ‘Low Risk – moderate sexual trauma’, ‘Moderate Risk’, and ‘High Risk’. Similarly, three classes were also identified for the Malaysian sample: ‘Low Risk’, ‘Moderate Risk’, and ‘High Risk’. Membership of ‘Moderate Risk’ was associated with male sex in both samples, and with older age and lower levels of parental education attainment in the Malaysian sample. No correlates of ‘High Risk’ class were identified in either sample. Membership of the ‘High Risk’ class was significantly associated with probable PTSD diagnosis in both samples, while membership of the ‘Moderate Risk’ class was associated with probable PTSD diagnosis in the Malaysian sample. Conclusion: Findings from this study correspond with Western studies indicating co-occurrence of PTEs to be common and to represent a salient risk factor for the development of PTSD.